Manajemen Risiko Dalam Pengadaan Konstruksi Pada Masa Transisi E-Katalog Versi 6: Studi Kasus DPUPKP Kabupaten Sleman Tahun 2025: (Studi Kasus DPUPKP Kabupaten Sleman Tahun 2025) - Aruminingsih, Ambar; Asakdiyah, Salamatun (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
This research analyzes the risks in construction procurement during the transition from e-Catalog Version 5 to Version 6 at the Dinas Pekerjaan Umum, Perumahan dan Kawasan Permukiman (DPUPKP) of Sleman Regency. Using a qualitative approach with thematic analysis and the ISO 31000:2018 framework, the study finds that the dominance of e-purchasing creates systemic disruptions due to unready digital infrastructure. Key themes such as unprepared catalog showcases, slow product curation, and insufficient supplier training led to decreased budget absorption and delays in physical project activities. Most risks were external and beyond the local government's control. The study recommends developing mitigation scenarios, strengthening local institutional capacity, and advocating for more inclusive transition policies from the central government.